2017
DOI: 10.3389/fnins.2017.00011
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Bcl-2 and Its Promoter Signals in CD4+ T Cells during Neuromyelitis Optica Remission

Abstract: The homeostatic balance between production and elimination of CD4+ T cells in peripheral blood plays an important role in patients with neuromyelitis optica (NMO). The objective of the present study was to evaluate the anti-apoptosis genes Bcl-2 and its promoter signal (nuclear factor kappa-light-chain-enhancer of activated B cells, NFκB) in CD4+ T cells. Healthy subjects (HS, n = 25) and patients with multiple sclerosis (MS) (n = 25) and NMO (n = 30) in remission were consecutively enrolled in this prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…However, stressors cause lower HPI (hypothalamus-pituitary-interrenal) response in bold than in shy fish [ 20 , 52 , 66 , 67 ]. In terms of neurotransmitters, lower brain serotonergic activity and higher dopaminergic activity characterize proactive (bold) individuals, while reactive animals (shy) display higher serotonin and lower dopamine levels, which may also contribute to the behavioral differences in these profiles [ 20 , 52 , 66 , 68 , 69 ]. In this respect, we believe psychoactive drugs have a different effect on physiology and behavioral profiles.…”
Section: Discussionmentioning
confidence: 99%
“…However, stressors cause lower HPI (hypothalamus-pituitary-interrenal) response in bold than in shy fish [ 20 , 52 , 66 , 67 ]. In terms of neurotransmitters, lower brain serotonergic activity and higher dopaminergic activity characterize proactive (bold) individuals, while reactive animals (shy) display higher serotonin and lower dopamine levels, which may also contribute to the behavioral differences in these profiles [ 20 , 52 , 66 , 68 , 69 ]. In this respect, we believe psychoactive drugs have a different effect on physiology and behavioral profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Further support for a key role of NTS astrocytes in the control of feeding comes from a series of studies on endozepines. NTS astrocytes (and tanycyte like cells of the area postrema known as vagliocytes [111] ) express octadecaneuropeptide (ODN) [112] an endozepine cleaved from acyl-CoA-binding protein (ACBP) which acts to supress food intake [113] . Delivery of ODN into the 4V supresses food intake in rats and induces c-FOS expression in the NTS [112] .…”
Section: Regulation Of Physiology By Nts Astrocytesmentioning
confidence: 99%
“…Paclitaxel, a microtubule stabilizing agent commonly used to treat patients with breast, ovarian, lung, or other cancers, causes a primarily sensory neuropathy (Gornstein and Schwarz, 2014). It has been suggested that paclitaxel elicits a degenerative cascade similar to that observed after mechanical axon injury (Fukuda et al, 2017; Gornstein and Schwarz, 2014; Wang et al, 2002; Wang et al, 2004). However, the molecular mechanism for paclitaxel-induced degeneration is not understood, and there are currently no treatments available for this common disorder.…”
Section: Introductionmentioning
confidence: 96%